Patient compliance to glaucoma therapeutics: a Portuguese overview - Reis Lopes, Maria José (2018)
Framework: glaucoma is one of the main causes for irreversible blindness. Proper treatment requires high levels of compliance to therapeutics. Most glaucoma patients do not comply with their treatment and that has been correlated with glaucoma progression. Aim: to evaluate patient’s compliance to glaucoma therapeutics. Methodology: an observational, cross-sectional and descriptive study was developed. Outpatients with glaucoma were enrolled and screened before follow-up medical appointment with an observational grid while applying antiglaucomatous drugs. After the treatment, patients were interviewed to understand their skills and difficulties in performing glaucoma treatment. Results: from 51 outpatients enrolled, 39% of them did not know the medication’s name used; 59% did not perform hand washing prior to the procedure; 73% leaned the vial tip contacting the eye; 25% did not apply the medication to the conjunctival sac; in 63% of the subjects used more than one drop; the majority of patients, 57%, did not wait the appropriate time between applications when two or more drugs were prescribed. Conclusion: the results suggest the need to implement individual or group strategies that enable patients with glaucoma to correctly perform their treatment.